The Pictures of Hans Vredeman de Vries in the Council's Grand Chamber of the Main City Town Hall in Gdansk (Bulletin KNOB, 2001)
Hans Vredeman arrived in Gdansk in 1592. He was commissioned by the City Council as the architect of fortifications. On October 1, 1592, Vredeman signed a one-year contract' as the city architect. His task was to build fortifications at the mouth of the Vistula River - Wisloujscie and the Motlawa. A year later it was Anton van Obbergen's project that was approved; Vredeman was dismissed.In 1594 the Council commissioned him to paint Orpheus among beasts for the Court of Artus. The picture did not survive. We know that it hung on the south-western wall of the Court. At that time the city authorities undertook to change the decorations in the stately rooms of the Main City Town Hall. It was Vredeman who was commissioned to perform this task. Seven pictures have survived until our times.It took two years - 1594 and 1595 - to redecorate the Council's Great Chamber. The artist was assisted by his son Paul. The last trace of Vredeman's stay in Gdansk is a record in the books of December 30, 1595. In the Council's Great Chamber we deal with Vredeman's only cycle of paintings that has survived almost intact. Karl van Mander mentions eight pictures. The first picture presents Justice and Injustice. The second picture of the cycle is Council. Piety is the third picture. The next picture shows Concord. Liberty is the subject of the picture that follows. The sixth painting, done by Vredeman for the Council's Room, is titled Constantia, i.e. Constancy. The last picture of the cycle is Last Judgement. In his description of the seven mural pictures, van Mander adds an eighth that served as a screen in front of the fireplace. From his detailed description the picture can be given the title Ratio’.